The role of PET and MRI in evaluating the feasibility of skin-sparing mastectomy following neoadjuvant therapy. - MALYA, FATMA ÜMİT; MALYA, FATMA ÜMİT; KADIOGLU, HÜSEYİN; KADIOĞLU, HÜSEYİN; BEKTASOGLU, HÜSEYİN KAZIM; BEKTAŞOĞLU, HÜSEYİN KAZIM; Gucin, ZÜHAL; GÜCİN, ZÜHAL; YILDIZ, S; YILDIZ, ŞEYMA; GUZEL, MEHMET; GÜZEL, MEHMET; et al. (My University, 2018)
Abstract Objective: To investigate the role of positron emission tomography (PET) and magnetic resonance imaging (MRI) in evaluating the feasibility of skin-sparing mastectomy in patients with locally-advanced breast cancer (LABC) who will undergo neoadjuvant chemotherapy (NAC) by evaluating the sensitivity and specificity of PET and MRI compared with skin biopsy results before and after NAC treatment. Methods: Patients with LABC who were treated with NAC between November 2013 and November 2015 were included in this study. Demographic, clinical, radiological and histopathological features of the patients were recorded. Results: A total of 30 patients were included in the study with a mean age of 52.6 years (range, 35– 70 years). Sensitivity and specificity for detecting skin involvement in LABC was 100%/10% (62%/ 85%) with MRI and 60%/80% (12%/92%) with PET before (after) NAC, respectively. When radiological skin involvement was assessed in relation to the final histopathological results, the preNAC PET results and histopathological skin involvement were not significantly different; and there was no difference between postNAC MRI and histopathological skin involvement. Conclusions: As preNAC PET and postNAC MRI more accurately determined skin involvement, it might be possible to use these two radiological evaluation methods together to assess patient suitability for skin-sparing mastectomy in selected patients.
Keywords: Breast cancer; MRI; PET; Skin-sparing mastectomy